Ongoing astrometric microlensing events of two nearby stars - Klüter, Jonas; Bastian, Ulrich; Demleitner, Markus; Wambsganß, Joachim (Astronomy and astrophysics, 2018)
Context. Astrometric microlensing is an excellent tool to determine the mass of stellar objects. By measuring the astrometric shift of a background source star in combination with precise predictions of its unlensed position and of the lens position, gravitational lensing allows to one determine the mass of the lensing star with a precision of 1%, independently of any prior knowledge.Aims. Making use of the recently published Gaia Data Release 2 (Gaia DR2) we predict astrometric microlensing events by fore-ground stars of high proper motion passing by a background star in the coming years.Methods. We compile a list of approximately 148 000 high-proper-motion stars within Gaia DR2 with µtot > 150 mas yr−1. We then search for background stars close to their paths and calculate the dates and separations of the closest approaches. Using color and absolute magnitude, we determine approximate masses of the lenses. Finally, we calculate the expected astrometric shifts and magnifications of the predicted events.Results. We detect two ongoing microlensing events by the high-proper-motion stars Luyten 143-23 and Ross 322 and predict closest separations of (108.5 ± 1.4) mas in July 2018 and (125.3 ± 3.4) mas in August 2018, respectively. The respective expected astrometric shifts are (1.74 ± 0.12) mas and (0.76 ± 0.06) mas. Furthermore, Luyten 143-23 will pass by another star in March 2021 with a closest separation of (280.1 ± 1.1) mas, which results in an expected shift of (0.69 ± 0.05) mas.
Gesehen am 30.07.2018